Design of a TDI CCD data acquisition system - Yu, Ran; Liu, Youjun; Lu, Jianrong (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
In this paper, the system configuration and design scheme of a data acquisition system based on a time delay integration and charge-coupled device (TDI CCD) are introduced. The circuit design principle and implementation of TDI CCD driving pulses are presented, which are confirmed by Quartus II simulation with the Verilog Hardware Description Language (Verilog HDL). The output signals of TDI CCD are first conditioned with the technique of correlated double sampling (CDS), then converted with an analog-to-digital (A/D) chip, and finally transferred to computer though a USB interface. The system can be used in human body imaging, such as head, teeth and palm and so on.